OSELTAMIVIR AS ANTIVIRAL THERAPY OF INFLUENZA A(H1N1)pdm09 IN CHILDREN AND ADULTS - L. V. Osidak; V. V. Zarubaev; O. I. Afanasyeva; L. V. Voloshuk; V. V. Gonchar; М. М. Pisareva; E. G. Golovacheva; E. А. Dondurey; V. S. Afanasyeva; V. F. Suhovetskaya; E. V. Obraztsova; E. G. Rozhkova; et al. (LLC "Diagnostics and Vaccines", 2016)
In this article are presented the results of comparative of experimental (on cell cultures) study of the influenza virus strains sensitivity to neuraminidase  inhibitor - Oseltamivir and blocker of M-canal - Rimantadin аnd the results of study effectiveness of the inclusion in the complex therapy of 331 hospitalized patients (children and adults) rapy of А(Н1N1)pdm09 antiviral drug - inhibitor of neuraminidase Oseltamivir that occurred during the epidemic seasons 2009-2010 and 2015-2016  in terms of observational clinical studies.  It is shown that this drug, can be successfully used in the treatment of children and adults with influenza А(Н1N1)pdm09 during 8-9 years after beginning of pandemic cycle.